Longitudinal associations between conflict monitoring and emergent academic skills: An event‐related potentials study. Issue 4 (26th November 2018) - Isbell, Elif; Calkins, Susan D.; Cole, Veronica T.; Swingler, Margaret M.; Leerkes, Esther M.
Abstract: Identifying the links between specific cognitive functions and emergent academic skills can help determine pathways to support both early academic performance and later academic achievement. Here, we investigated the longitudinal associations between a key aspect of cognitive control, conflict monitoring, and emergent academic skills from preschool through first grade, in a large sample of socioeconomically diverse children ( N  = 261). We recorded event‐related potentials (ERPs) during a Go/No‐Go task. The neural index of conflict monitoring, ΔN2, was defined as larger N2 mean amplitudes for No‐Go versus Go trials. ΔN2 was observed over the right hemisphere across time points and showed developmental stability. Cross‐lagged panel models revealed prospective links from ΔN2 to later math performance, but not reading performance. Specifically, larger ΔN2 at preschool predicted higher kindergarten math performance, and larger ΔN2 at kindergarten predicted higher first‐grade math performance, above and beyond the behavioral performance in the Go/No‐Go task. Early academic skills did not predict later ΔN2. These findings provided electrophysiological evidence for the contribution of conflict monitoring abilities to emergent math skills. In addition, our findings suggested that neural indices of cognitive control can provide additional information in predicting emergent math skills, above and beyond behavioral task performance.